Reduction in Stroke After Transient Ischemic Attack in a Province-Wide Cohort Between 2003 and 2015. (22nd May 2021) - Wang, Ryan; Kapoor, Arunima; Lindsay, Patrice; Goia, Cristina; Yu, Amy Y. X.; Gladstone, David J.; Swartz, Richard H.
ABSTRACT: Background: Improvements in management of transient ischemic attack (TIA) have decreased stroke and mortality post-TIA. Studies examining trends over time on a provincial level are limited. We analyzed whether efforts to improve management have decreased the rate of stroke and mortality after TIA from 2003 to 2015 across an entire province. Methods: Using administrative data from the Canadian Institute for Health Information's (CIHI) databases from 2003 to 2015, we identified a cohort of patients with a diagnosis of TIA upon discharge from the emergency department (ED). We examined stroke rates at Day 1, 2, 7, 30, 90, 180, and 365 post-TIA and 1-year mortality rates and compared trends over time between 2003 and 2015. Results: From 2003 to 2015 in Ontario, there were 61, 710 patients with an ED diagnosis of TIA. Linear regressions of stroke after the index TIA showed a significant decline between 2003 and 2015, decreasing by 25% at Day 180 and 32% at 1 year (p < 0.01). The 1-year stroke rate decreased from 6.0% in 2003 to 3.4% in 2015. Early (within 48 h) stroke after TIA continued to represent approximately half of the 1-year event rates. The 1-year mortality rate after ED discharge following a TIA decreased from 1.3% in 2003 to 0.3% in 2015 (p < 0.001). Interpretation: At a province-wide level, 1-year rates of stroke and mortality after TIA have declined significantly between 2003 and 2015, suggesting that efforts to improve management may have contributed toward the decline in long-term risk of stroke and mortality. Continued efforts are needed to further reduce the immediate risk of stroke following a TIA.